HUBUNGAN PERSEPSI SISWA TENTANG GURU BAHASA INDONESIA, MINAT BELAJAR, DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR SISWA DI MTsN SEMANU GUNUNGKIDUL - Isnaini, Muhammad Yusuf (Diksi, 2019)
(Title: Perceptions About Indonesian Teachers, Learning Interests, and Learning Motivation with Student Learning Achievements in MTsN Semanu Gunungkidul). Teachers have a big role in fostering positive perceptions about Indonesian language learning. This positive perception will foster interest in students to learn Indonesian seriously. The purpose of this study was to analyze the relationship between students 'perceptions of Indonesian teachers, students' interests and motivations in learning Indonesian subject matter with the learning achievements of Gunungkidul's 3 MTsN students. The correlation between students 'perceptions of Indonesian language teachers, students' interests and motivation in learning Indonesian language material with the students 'achievement in Gunungkidul's MTsN 3 is evidenced by the students' perceptions of Indonesian Language teachers (X1), which are included in quite a category (63.10%). Student perceptions of Indonesian language teachers have a positive relationship with student learning achievement as indicated by the value of b1 of 0.413. The relationship between students' perceptions of Indonesian teachers and student learning achievement is significant as indicated by the value of tcount (8,352) greater than ttable (1,960).Keywords: perception, interest, motivation, learning achievement